Patterns and outcomes of chest injury among adult patients treated at Hawassa university comprehensive specialized hospital, Hawassa sidama, Ethiopia:: Retrospective record review - Nademo, Siyasebow; Dahir , Abdulkadir; Dodgion , Christopher (Ethiopian Journal of Medical and Health Sciences, 2025)
Introduction: Trauma is a major global health concern, causing 4.4 million deaths annually, withthoracic injuries accounting for 25% of deaths. Developing countries disproportionately bear thesedeaths due to inadequate post-trauma measures. Methods: Retrospective chart review study was conducted at Hawassa University ComprehensiveSpecialized Hospital among 111 chest injury patients from August 01/2021 to August 31/2023. Datawere collected using structured questionnaires from the trauma registry, 24-hour reports, and patientcharts and collected by trained nurses. The collected data were entered, cleaned, edited, and analyzedusing SPSS version 25.0 statistical software. Results: A total of 111 chest injury patients’ charts were included in the analysis. About threefourths (74.77%) were males, and 28 (25.23%) were females. Blunt trauma (77.5%, n = 86) was themost common type of injury, with road traffic crashes (59.5%, n = 66) being the most commonmechanism. Rib fracture (n = 39, 35.14%) was the most common injury, followed by hemothorax (n =37, 33.33%), hemopneumothorax (n = 32, 28.83%), and flail chest (n = 18, 16.22%). On univariateanalysis, comorbidity (P <0.001), blunt mechanism (P = 0.039), hemopneumothorax (P = 0.006), flailchest (P = 0.021), pulmonary contusion (P = 0.014), development of complication (P <0.001), andextra thoracic injuries (P = 0.013) were associated with mortality. Conclusion: This study found that one in ten chest injury patients died in a hospital, with road traffic accidents being the main cause. Most patients sustained blunt chest injuries and death was associated with chronic diseases, hemopneumothorax, multiple injuries, and complications.